Ajaran Isyrāqi: Studi Kritis-Epistemologis Filsafat Iluminasi Suhrawardi - Hasna Ulfa Nur Laini; Achmad Khudori Soleh (Fakultas Ushuluddin, Universitas Darussalam Gontor, 2024)
This research examines the epistemology of Isyrāqi philosophy critically-systematically, examining details from the source of thought, methods to verification and implications of Suhrawardi's Isyrāqi philosophy. In explaining, the author uses qualitative research, which is presented descriptively-analytically with an epistemological-philosophical perspective Nicholas Rescher. As a result, this research shows three things: First, Isyrāqi philosophy comes from the extraction of five major schools; pre-Islamic philosophy (Greece), Islamic peripatetik philosophy, especially Ibn Sina, ancient Iranian thought, Sufistic thought of Mansur al-Hallaj and al-Ghazali, and Zoroastrianism. Second, to reach isyrāqi knowledge, Suhrawardi requires to involve spiritual practice (mujāhadah) and asceticism, which is detailed in four stages in an orderly manner. Including the preparation stage, the reception stage, then the development stage (proof), and finally the immortalization stage. Third, for Suhrawardi, knowledge can be said to be final by combining two things: 1) The intellectual power of reason (discursive knowledge), and 2) Intuitive knowledge; witnessing and revelation (musyāhadah wal mukāsyafah). Light as a symbol of true truth in Isyrāqi teachings, and the tool to obtain light is intuition, while the ratio is used to explain the intuition. Suhrawardi was not satisfied with the peripatetik concept of emanation which emphasizes the role of the intellect ('aql) in the process of reaching knowledge. According to him, the role of intuition (dzawq) and mystical revelation manifested through absolute light are fundamental realities. The implications of Suhrawardi's Isyraqī ultimately paved the way for the development of Islamic philosophy afterwards, among others it is shown in the thoughts of Ibn Arabi (1165-1240) and Mulla Sadra (1573-1641).